MicroRNA-34a enhances T cell activation by targeting diacylglycerol kinase ζ. - Jinwook Shin; Danli Xie; Xiao-Ping Zhong (PLoS ONE, 2013)
The engagement of the T cell receptor (TCR) induces the generation of diacylglycerol (DAG), an important second messenger activating both the Ras/Erk and PKCθ/NFκB pathways. DAG kinases (DGKs) participate in the metabolism of DAG by converting it to phosphatidic acid. DGKζ has been demonstrated to be able to inhibit DAG signaling following TCR engagement. Deficiency of DGKζ increases the sensitivity of T cells to TCR stimulation, resulting in enhanced T cell activation ex vivo and in vivo. However, the mechanisms that control DGKζ expression are poorly understood. Here we demonstrate that DGKζ mRNA is a direct target of a cellular microRNA miR-34a. The DGKζ transcript is decreased, whereas the primary miR-34a is upregulated upon TCR stimulation. Ectopic miR-34a expression suppresses DGKζ protein expression through the seed match binding to both the 3' untranslated region and coding region of DGKζ mRNA, leading to increased ERK1/2 phosphorylation and surface expression of the T cell activation marker CD69 following TCR cross-linking. In contrast, overexpression of a miR-34a competitive inhibitor increases DGKζ expression and suppresses TCR-mediated T cell activation. Together, our data demonstrate that miR-34a is a negative regulator for DGKζ and may play an important role in regulating T cell activation.